Investigating the role of hyperexpressed HCN1 in inducing myocardial infarction through activation of the NF-κB signaling pathway - Liang Xiao; Zhang Jie; Luo Ya (Open Life Sciences)
We investigated the protective effect of the NF-κB inhibitor, pyrrolidine dithiocarbamate (PDTC) on cardiomyocyte injury induced by HCN1 channel overexpression, and explored the underlying mechanisms. An HCN1 overexpression vector was constructed and transfected into H9C2 cells, followed by PDTC treatment. The experiments comprised the following groups: control, control + PDTC, overexpression negative control, HCN1 overexpression (HCN1-OE), and combined HCN1-OE + PDTC groups. Cell proliferation was assessed using the CCK8 assay, while apoptosis and reactive oxygen species (ROS) levels were measured by flow cytometry. ELISA kits were used to determine the levels of malondialdehyde, superoxide dismutase, and interleukin-1 beta. The HCN1-OE group exhibited increased apoptosis, elevated ROS, and decreased survival. Western blot (WB) analysis revealed increased levels of p65, p-IκB, IKKβ, NLRP3, Beclin-1, and LC3 II/I proteins in the HCN1-OE group. PDTC treatment for 48 h post-HCN1-OE resulted in improved cell viability, reduced apoptosis, and decreased ROS in the HCN1-OE + PDTC group. Immunofluorescence and WB analysis indicated a reduction in HCN1 and NF-κB pathway protein levels in the HCN1-OE + PDTC group. In conclusion, PDTC provided protection against HCN1-induced cardiomyocyte injury, potentially by modulating inflammatory cytokines and regulating the IKKβ/IκB/NF-κB signaling pathway.